Perception of Corporate Identity in Croatian and Slovakian Wood Processing and Furniture Manufacturing Companies (University of Zagreb, Faculty of Forestry and Wood Technology, 2010)
In this paper we have researched the perception of corporate identity in wood processing and furniture manufacturing companies in Croatia and Slovakia. The research was conducted as a survey using questionnaires, which contained general information about the enterprise and 10 questions regarding the perception of corporate identity. In Croatia 210 enterprises for wood processing and furniture manufacturing were surveyed and 300 enterprises in Slovakia. Only 43 (20.47 %) of them answered to all the questions, of which 35 (16.67 %) were taken into consideration in Croatia. In Slovakia 80 (26.60 %) enterprises answered to the questions, of which 59 (19.67 %) were taken into consideration. The given data were analyzed statistically using χ2-test. The main hypothesis was that there was no significant difference in the perception of corporate identity in Croatian and Slovakian wood processing and furniture manufacturing firms. The results showed that corporate identity in Croatian and Slovakian wood processing and furniture manufacturing companies was mostly defined and identified with visual presentation of the company, image and reputation and differentiation in the market. At the same time, most respondents thought that corporate identity was mostly made of the company design, outward communication and company’s philosophy. In general, the only significant difference between answers of Croatian and Slovakian respondents was established for the question 4 (How would you define „Corporate Identity” in your own words).